AKTIFITAS YAYASAN BUDDHA TZU CHI DI PADANG: TINJAUAN SEJARAH LEMBAGA SOSIAL TAHUN 2003-2013 - SURYAWAN, HENDRO; Naldi, Hendra; Erawati, Meri (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Buddha Tzu Chi in Padang City stands on 6 June 2003, the first pioneers that bring Buddha Tzu Chi is Mr. Ferryanto Gani as long as Head of Tzu Chi Padang, after that Mr. Sjirwan Hamzah, Mr. Widya Kusuma Lourenzi, Mr. Chaidir. As social institutions Buddha Tzu Chi in Padang City is very helpfully to solve the social problems that have been found in society. If look at the point of Buddha Tzu Chi Institutions in Padang City, it was stand up by peoples Tionghoa, it is something unique where minority of people can participated in social activities.The result of researchâs shows that 1) Buddha Tzu Chi Institutions in Padang City was valid as one as Institutions based on Notary Public Certificates Number 109 due to opening the official of relationships / representatives Buddha Tzu Chi Institutions of Indonesia Number C-HT.01.09-46 dates one September two thousands and three (1-9-2003) Number 4, it was print out by notary public Dr. Irawan Soerodjo, SH, M.Si, as notaries in Jakarta. 2) As independent institutions, Buddha Tzu Chi Institutions in Padang City have a backgrounds that the pioneers wishes to serve of themselves to help and solves social problems of society by focusing to social problems areas. The Progress of these institutions from 2003 until 2013 it was carry out of many wisdoms including about chooses and appointment of the staff institutions that doing based from the results of consultations in one time from five years. 3) As social institutions, Budha Tzu Chi also participated to solve social problem in some part of society lives by pour some helping with doing activities likes; activity in charities, activity consultation of healthy, activity in educations, and also activity in everlasting areas. Â Â